Fault tolerant control using Gaussian processes and model predictive control - Yang, Xiaoke; Maciejowski, Jan M. (Zielona Góra: Uniwersytet Zielonogórski)
Essential ingredients for fault-tolerant control are the ability to represent system behaviour following the occurrence of a fault, and the ability to exploit this representation for deciding control actions. Gaussian processes seem to be very promising candidates for the first of these, and model predictive control has a proven capability for the second. We therefore propose to use the two together to obtain fault-tolerant control functionality. Our proposal is illustrated by several reasonably realistic examples drawn from flight control.
Keywords: fault-tolerant control; Gaussian process; model predictive control; aircraft control; probabilistic modelling